Reflection of The Socio-Economic Developments in Kazakhistan After USSR to Turkey (Journal of Oriental Studies, 2022)
The process of the collapse of the USSR, which began under the leadership of the Baltic countries, ended with the declaration of independence of the countries under its rule in 1991. Kazakhstan, which has been in the mosaic of the USSR for more than 70 years, declared its sovereignty on October 25, 1990, and independence on December 16, 1991. In the elections held on December 1, 1991, Nursultan Nazarbayev was elected the first President of independent Kazakhstan. The first country to recognize it was the Republic of Turkey.  Before this period, "social, cultural, and economic" relations between the two countries were practically non-existent. After Kazakhstan gained independence, mutual political contacts resumed. Agreements have been signed with Turkey in many areas. A great contribution to the prosperity of Kazakhstan today was made by the first President of the country, Nursultan Nazarbayev. Turkey has established close cooperation with Kazakhstan, which is in our heart and cultural geography, and has strengthened the relationship that it has been striving for years.This study included field research and a literature review. In the study, the connection between Kazakhstan and Turkey was interrupted during the period of Soviet Russia. With the collapse of the USSR, very important opportunities appeared. The importance of this study lies in the fact that it reveals the importance of these relations between the two countries. A point will be given for further research on the connection between Kazakhstan and Turkey.Keywords: USSR, Kazakhstan, Turkey, Trade, Culture.